Application of Electrical Resistivity Method with Peak and Flat Base Electrodes to Detect A Potential Water Leakage Underneath A Water Pool in Kiara Payung, Sumedang, West Java - Mutiara Nurul Azizah; Ayunda Aulia Valencia; Agus Kuswanto (Jurnal Geosains Terapan, 2023)
This study aims to detect potential leakage underneath a water pool made of concrete using the electrical resistivity method with peak and flat base electrodes. Peak electrodes cannot be used on hard materials such as concrete because they can damage the concrete structure, while flat base electrodes can be used without causing any damage to the structure. This study was performed using a single profile, along which electrical resistivity measurements were conducted with different electrode combinations: all peak electrodes, a combination of peak and flat base electrodes, and all flat base electrodes. The maximum profile length was 117.5 meters with a spacing between electrodes of 2.5 meters and using a total of 48 electrodes. The measured apparent resistivity was inverted using the least-square and robust constraint inversion methods to obtain 2D true resistivity sections. An analysis of the 2D sections was conducted based on the resistivity profile, model errors, and ability to resolve the water pool geometry. The results show that the inverted model using the robust constraint method with flat base electrodes has the best result, which exhibits a clear boundary between the water pool and its surrounding soil, has a smaller error, and is able to resolve the water pool geometry compared to other models. This inversion result indicates no leakage occurs underneath the water pool. Therefore, the electrical resistivity method using flat base electrodes can be used for long-term maintaining the water pool in the study area and should be used in other geoelectric resistivity studies on hard surfaces.